Anticipating global and diffuse risks to prevent conflict and governance breakdown: lessons from the EU's southern neighbourhood. Issue 7 (3rd October 2021) - Magen, Amichai; Richemond-Barak, Daphné
ABSTRACT: Where societies display sufficient resilience to global and diffuse risks they are able to avoid tipping-over into governance breakdown and violent conflict. Similarly, if external actors such as the EU wish to build resilience in Europe's volatile neighbourhood, they require a systematic understanding of global and diffuse risks and tipping-points in order to develop long-term resilience-building strategies. But how should global and diffuse risks and tipping-points be conceptualized and understood? How can policy-makers anticipate global and diffuse risks to avoid governance breakdown and violent conflict in areas of limited statehood? This article addresses these questions. First, it argues, it is only by systematically integrating global and diffuse risks into explanatory logics of governance breakdown and violent conflict that we can develop better predictive models and resilience-building strategies. Second, it articulates a six-cluster typology of global and diffuse risks. Lastly, it demonstrates that in areas of limited statehood societies confront three distinct types of tipping-points that can overwhelm societal resilience. EU early-warning and resilience-fostering policy ought to distinguish between them and prepare to address each type.